2012
DOI: 10.1042/cs20110665
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin administration prevents the changes induced by a fructose-rich diet on rat liver metabolism and the antioxidant system

Abstract: In the present study, we investigated the role of NADPH oxidase in F (fructose)-rich-diet-induced hepatic OS (oxidative stress) and metabolic changes, and their prevention by apocynin co-administration. Wistar rats were fed for 21 days on (i) a control diet, (ii) a control diet plus 10% F in the drinking water, (iii) a control diet with apocynin in the drinking water (CA) and (iv) F plus apocynin in the drinking water (FA). Glycaemia, triglyceridaemia, NEFAs (non-esterified fatty acids) and insulinaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 46 publications
2
38
1
Order By: Relevance
“…Similarly, fructose-related activation of cardiac NF-κB was previously reported [47], but in contrast to our results obtained in females, it was not observed in the VAT of young male rats [48]. Several researchers reported elevated IL-1β and TNFα in the liver [49] and plasma [50][51][52] after fructose feeding. In the study of Hsieh [53], dietary fructose was shown to elicit TNFα concentrations in the adipose tissue of male rats.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Similarly, fructose-related activation of cardiac NF-κB was previously reported [47], but in contrast to our results obtained in females, it was not observed in the VAT of young male rats [48]. Several researchers reported elevated IL-1β and TNFα in the liver [49] and plasma [50][51][52] after fructose feeding. In the study of Hsieh [53], dietary fructose was shown to elicit TNFα concentrations in the adipose tissue of male rats.…”
Section: Discussioncontrasting
confidence: 85%
“…A number of studies have demonstrated decreased expression or activity of antioxidative enzymes after fructose consumption and a concomitant presence of oxidative stress [49,51,65]. The oxidative environment evoked by fructose overconsumption might be an explanation for decreased glucocorticoid receptor's hormone-binding capacity and affinity observed in our previous study [44].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Protein carbonyl and GSH liver contents were determined as described elsewhere [22]. Briefly, both components were spectrophotometrically measured (at 366 nm for protein carbonyl groups and 414 nm for GSH) and results were expressed in nmol of carbonyl residues per mg of protein based on the molar extinction coefficient of 21,000 M −1  cm −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Total liver RNA was isolated using the TRIzol Reagent (Gibco-BRL, Rockville, MD, USA) as previously described [22]. The integrity and quality of the isolated RNA were checked by agarose-formaldehyde gel electrophoresis and by measuring the 260/280 nm absorbance ratio.…”
Section: Methodsmentioning
confidence: 99%